![(2)/(5)x\text{-3=-17}](https://img.qammunity.org/2023/formulas/mathematics/college/2sfcweqob5eyy6ukrsoowo7sqgwtex2k2x.png)
To solve the equation, you must put the variable on one side and the other terms on the other side, then make its coefficient equal to 1
Add 3 to both sides
![\begin{gathered} (2)/(5)x-3+3=-17+3 \\ (2)/(5)x=-14 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/70sigpmuylzccmcoubrroc6ne98d5jhwkr.png)
Now multiply both sides by 5 to cancel the denominator on the left side
![\begin{gathered} (2)/(5)x*5=-14*5 \\ 2x=-70 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/pesr5dvf6hon9bp085t5p5zidtfuz145wi.png)
Divide both sides by 2 to find x
![\begin{gathered} (2x)/(2)=-(70)/(2) \\ x=-35 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/uj11chev5ijqb7eri4vl1ukswdpiuvwxwp.png)
The solution of the equation is x = -35
The answer of no. 44 is x = -35